Corridors of the night - Perry, Anne, 1938- (William Monk, 2015)
One night, in a corridor of the Royal Naval Hospital in Greenwich, nurse Hester Monk is approached by a terrified girl.She's from a hidden ward of children, all subject to frequent blood-letting, and her brother is dying.While William Monk's River Police fight to keep London safe from gun-runners, Hester takes on a new role at the hospital, helping to administer a secretive new treatment.But she slowly realises that this experimental cure is putting the lives of the children at risk.Attempting to protect the young victims, she comes under threat from one rich, powerful, and very ill man who is desperate to survive...